Design, manufacture and commissioning of a low pressure quasistatic bulge tester for skin and membrane tissue - Curry, Andrew Michael (Department of Mechanical Engineering, 2021)
The material properties of skin are of great importance to a variety of fields such as dermatology and reconstructive surgery. Relatively little infrastructure and expertise exists locally in South Africa for testing biological tissue. The difficulties of testing the material properties of skin are the non-uniformity and anisotropy across specimen location and subjects. This anisotropy is most commonly measured by tensile testing of samples cut in different orientations. However, the individual samples at different orientations would be extracted from slightly different locations on the same subject, which will naturally vary in response. Bulge testing is a method of determining response to tension in different directions at the same location, by applying biaxial tension. It uses a positive pressure applied to a peripherally clamped specimen to deform the specimen in a balloon type manner. In this project, bulge testing apparatus was designed and built for the purpose of testing skin and membrane tissue, under biaxial tension. The testing apparatus consists of a syringe pump to control inflation of a specimen, which is clamped in an inflation chamber. Digital Image Correlation (DIC) was used to capture the 3D deformation fields of the specimen, and hence infer the strain fields. To simplify commissioning testing, a commercial silicone elastomer suited for skin prosthetics, was used to manufacture specimens for uniaxial and bulge experimental testing. Two types of bulge specimens were manufactured, standard round specimens and elliptical specimens. The round specimens were used to compare their material response to uniaxial tests and the elliptical bulge specimens were used to simulate the anisotropic response of skin. The method of analysis used in this project is based on using DIC and curvature calculations at multiple points to calculate membrane stresses in principal directions. The method of calculating principal curvatures from DIC is adapted from the work by Machado et al. [1] that calculated Gaussian curvature using the first and second fundamental forms of a surface. In total 18 round, 6 elliptical and 10 uniaxial specimens were tested and the material properties were found to vary slightly between each specimen. The spread in data between the uniaxial and bulge tests was found to be very similar with the bulge data showing 10 % spread at 1.2 stretch and constant 8 % spread above 1.2 stretch and the uniaxial data showing increasing spread from 7 % to 15 %. The curvature results showed very clear principal directions of curvature for the elliptical specimens. This demonstrated that the method used in this project is capable of clearly extracting the orientations of stiffer fibre directions of skin and other collagenous tissue.